Exploring alternatives to selling farm ground under urban development pressures: a case study in Wichita, KS - Thornton, Lindsay (My University, 2026)
Farm ground is lost to development every year. If you live close to an urban area, you can see urban development creep out into the rural landscape in real time. Developers often come with deep pockets and seemingly endless resources. While the money may look attractive, exploring other options can help a farmer make a more informed decision. The purpose of this thesis is to provide a case study that evaluates tradeoffs and opportunity costs that agricultural producers face when they consider selling farm ground. The research focuses on counties in South Central Kansas that would be susceptible to development pressures from the Wichita area. This case study explores four alternative options to retaining the land despite urban development pressures. Those options are selling the land, relocating the farm to a neighboring county, enrolling in the Conservation Reserve Program with the USDA, or finding a tenant to farm the ground. The Net Present Value (NPV) of the interest earned from the investment is calculated over a 10-year time horizon. The NPV is then calculated to find the best option. This case study can provide some insight into the loss of farm ground every year and could be a resource for a farmer who is considering selling his farm ground. The results showed that relocating the farm to an adjacent county provided the best financial results, but there were more variables to consider. Factoring risk and liquidity, along with a person’s emotional tie to the ground they have potentially farmed for generations, doesn’t make the choice as clear-cut and easy to make. Also, the age of the farmer and what their financial goals are can also play a part in the decision-making process. This study is helpful for any farmer who is feeling the pressures of urban sprawl or has been approached to sell their land. It allows them to look at the options available for generating income that may provide financial stability for the future.
Keywords: Opportunity cost; Wichita Kansas; Case study; Land value; NPV; Urban sprawl